Investigation of Rota Virus Between Vaccinated and Unvaccinated Infants and Childern in Al-Najaf Governorate - Gihad, Zeena Kareem (Newinera Publisher, 2024)
The study aims to investigate Rota virus in vaccinated and unvaccinated infants and childern in Al-Najaf governorate. To achieve this goal, collect 684 samples from Al-Zahraa Teaching Hospital for Maternity and Children in Al-Najaf governorate, through the period from 7 January 2024 A.D. to 1 December 2024 A.D. This study has revealed that the rota virus can be detected in stool samples from infants and children patients.The detection of Rota virus infections in samples has occurred by using immunochromatographic test (Rota virus rapid test kit). The Rota virus antigens has been detected in (463 out of 684) or (68%) in patients while remain as not found or negative result with virus (221out of 684) or 32%. The present study show the distribution of infants and children patients according to age. The age of patients with viral infections showed that the highest frequency was in age group A1 (23%) and the lowest frequency was in age group A4 and A5 (18%). All patients age group were selected in order to ensure comparable frequency distribution. In this study showed the symptomes that linked with rota virus infections in both vaccinated and unvaccinated cases, The first dose of rotarix vaccine show high percentage associated mild diarrhea (72%) and low percentage in other gastroentrites symptoms (12%). While the result with second dose of rotarix vaccine show high percentage associated other gastroentrites symptoms (87%) and low percentage in severe diarrhea (2%).